Must-Have Capabilities for Enterprise Mobility: A South African Study - B-Abee Toperesu; Jean-Paul Van Belle (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Mobile devices represent a difficult information technology decision for organizations, commonly referred to as the “Bring-Your-Own-Device” (BYOD) issue. On the one hand, information is now potentially available anytime, anywhere and some business processes can be optimized dramatically. On the other hand, business processes have to be changed, security issues have to be addressed, and data management and governance become very difficult. This study presents some empirical research based on interviews with selected IS Managers. The goal of this paper is to assess both a 'desired state' of capabilities as well as some evidence regarding current readiness and capability levels among South African organizations. We conclude with a proposed list of the must-have capabilities for Enterprise Mobility.
Keywords: O33; 330; Enterprise Mobility; ICT; Innovation Capability; Bring Your Own Device (BYOD); Mobile Device Management